A CONDUCIVE ENVIRONMENT FOR THE IMPLEMENTATION OF THE ISLAMIC CRIMINAL LAW FROM THE PERSPECTIVE OF FIQH – A STUDY IN MALAYSIA - Ismail, Faisal Bin Husen; Sulong, Jasni Bin (International Journal of Research -GRANTHAALAYAH, 2017)
A conducive environment is a comfortable situation, harmonious as well as friendly in the relationship between government and communities upon enforcement of law. Therefore, the administration and enforcement of law towards society have to take account public’s benefit, either from religion perspective, customary or local culture. The ignorance of those elements will bring regulation towards injustice and discrimination. For that reason, comfortable environment was taken into account during Caliph Omar al-Khattab who have procrastinated the enforcement of law (cutting hand for criminals) during drought period on the reason of unconducive period. It was a difficult phase of life which some communities living in needs and pitiable, and the situation is not appropriate to penalize them for stealing foods. However, scholars nowadays only discuss upon the matter in term of its influence to dismiss the application of Islamic law but not in term to comprehend the reality and concept of conducive environment in the application of Islamic criminal law. Therefore, the polemic of conducive environment took place without any yard stick of the situation that well elaborated. Hence, in order to overcome the conflict, this paper is at aim to clarify the notion as well as features of conducive environment from the perspective of shariah law. The paper will lay out the situation to become as a mechanism in measuring the readiness and ability in applying the fair law. The methodology of the study is in a qualitative means by reviewing historical notes by using content analysis upon the Prophets Era as well as the period of Khulafa’ al-Rashidin. The data will be compared to contemporary epoch in understanding the similarity as well as the difference. The finding of the study is very significant to justify the appropriateness in the application of Islamic criminal law nowadays, whether its meet the need of shariah (maqasid al-shariah) or vice versa.